Diversity in the workplace : eye-opening interviews to jumpstart conversations about identity, privilege, and bias - Williams, Bärí A. (Tantor Media, Inc., 2021)
Contemporary and compassionate teachings for building true workplace diversity In order to create an inclusive working environment, it is important for companies to understand the experiences that diverse employees face in the workplace. Diversity in the Workplace is a guided tour of what it means to be a minority in today's labor force. Containing twenty-five real-life interviews, including stories of trailblazers fighting inequality, you'll be exposed to a slice of life you may not have been privy to. This book explores real world issues in a modern workday dynamic for members of marginalized communities and managers looking to equalize an imbalance. Diversity in the Workplace includes: - Exploring intersectionality-Learn about the diversity identities shaping disparity at work: Race, Gender, LGBTQ+, Age & Ability, and Religion & Culture. - Key takeaways-Each section is followed by summaries that encourage reflection and action. - Deep dive-Learn tips on how to have progressive conversations with colleagues, and build awareness with key terms such as "unconscious bias." Move toward a more fair and bias-conscious future with Diversity in the Workplace